A Case of Sublingual Gland Hypertrophy in the Setting of Submandibular Gland Aplasia Presenting as a Neck Mass - Colten Wolf; Richard Hubbell (Case Reports in Otolaryngology)
Background. Absence or aplasia of the major salivary glands is an uncommon diagnosis and is often associated with other congenital abnormalities. Agenesis of a single submandibular gland, however, is an even more rare phenomenon and can be associated with hypertrophy of other salivary glands. Methods. A 48-year-old female presented to the clinic with a left-sided neck mass below her mandible. Workup including a CT scan showed an absent left-sided submandibular gland and an enlarged sublingual gland protruding through the mylohyoid muscle. Results. The patient underwent a transoral resection of the mass with subsequent resolution of the mass. The pathology returned as normal salivary gland tissue. Conclusions. Sublingual gland hypertrophy is a very uncommon presentation for a patient with a neck mass. This situation can arise in the setting of submandibular gland aplasia and compensatory hypertrophy of other salivary glands.